Implementation of Non-Communicable Disesase Risk Factors Surveillance in Posbindu Surabaya based on Surveillance Attribute (Study in Surabaya) - Elyda Rahmayanti; Arief Hargono (Universitas Airlangga, 2017)
deaths and illnesses due to NCD has increased every year, so it is necessary to control NCD. NCD-based risk factor surveillance based on NCD-Integrated health care post (Posbindu) has been carried out in every Public health center (PHC) in Surabaya City, but it is still not optimal because not all PHC have Posbindu so that PTM risk factors are still not identified in each PHC working area in Surabaya City. This aims of this study to evaluate NCD risk factor surveillance system based on Posbindu surveillance attributes in Surabaya City in 2016. This study is an evaluative descriptive study. The research subject was a Posbindu-based NCD risk factor surveillance system with research informants, namely 16 program managers and 77 Posbindu cadres. Data collection was carried out by questionnaire and document study. The results showed that the NCD surveillance system in the city of Surabaya is simple, easily accepted (acceptability), has high sensitivity and stability, is timely, and produces quality data. Assessment of flexibility and positive predictive value cannot be done. The conclusion from this study is that the surveillance attributes are good enough, but there are problems in the surveillance system. Suggestions for overcoming the problem are community empowerment for the purchase of own tools compiled by Posbindu cadres, records of expert or laboratory confirmation of the results of the inspection, and maintenance of the NCD web portal network system.